Stability and deformation analysis of failed embankments founded on soft clays - Jitno, Hendra; Gofar, Nurly (Faculty of Civil Engineering, UTM, 2005)
This paper presents results of stability and deformation analysis of several, failed embankment case histories founded on soft clay. Different methods of limit equilibrium analysis (Fellenius, Bishop, Janbu and Spencer) adopted in computer program SLOPE/W were used to calculate the Factor of Safety of each embankment. A continuum approach utilising a finite difference computer program FLAG was also used to calculate the Factor of Safety and study the deformation behaviour of the embankment. The results obtained using both methods were compared with observations. The effect of analysis methods, variation of shear strength parameters of both fill and foundation soils on the Factor of Safety were also discussed. The variation of soil strength is a dominant factor in the slope stability analysis. The limit equilibrium method which satisfies both force and moment equilibrium give better prediction on the stability of the slope.